Biaxial stretch-induced structural evolution of polyethylene gel films: Crystal melting recrystallization and tilting. (15th February 2019) - Wan, Caixia; Chen, Xiaowei; Lv, Fei; Chen, Xin; Meng, Lingpu; Li, Liangbin
Abstract: The crystal structure evolution of polyethylene (PE) gel films containing paraffin oil are studied with wide-angle X-ray scattering (WAXS) during sequentially biaxial stretching at the temperature around the melting point. Also, the surface morphologies of films after biaxial stretching are characterized by scanning electron microscope (SEM). During machine direction (MD) stretching process, the crystal structure is transformed from lamellar stacks to fibrillar crystals through melting recrystallization. While for transverse direction (TD) stretching, there exist three kinds of deformation mechanisms determined by draw ratio in MD ( λ MD ), i.e., transformation of weakly oriented crystals into fibrillar crystals by melting recrystallization at small λ MD ; with moderate λ MD, the fibrillar crystals in MD are tilted towards TD; at larger λ MD, the microfibrils are teared into thinner ones or fibrillar crystals, inclining to TD. Finally, the crystal morphology diagram is summarized in two-dimensional (2D) strain space, serving a roadmap for processing of PE microporous membranes. Graphical abstract: Image 10 Highlights: The structure evolution of PE gel films during sequentially biaxial stretching is characterized by WAXS. A morphology diagram in 2D strain space is proposed. Deformation mechanisms in TD stretching are revealed and defined into three regions according to λ MD .